Implikasi Hukum Perkawinan Beda Agama Berdasarkan UU No. 1 Tahun 1974 Tentang Perkawinan Dihubungkan Dengan UU No.23 Tahun 2006 Tentang Administrasi Kependudukan - Nina Yayu Maesaroh (Jurnal Media Justitia Nusantara, 2016)
Abstract. The Law No. 23 of 2006 on Population Administration (Adminduk) allows couples registered marriages of different religions through the determination of the origin of the Court On one side of the Law No. 1 of 1974 on Marriage states that marriage should be the same religion, and beyond that is not valid, but on the other hand Article 35 (a) of Act No. 23 of 2006 on Population Administration to allow it through determination. This study aimed to determine the consideration of the judge in determining the application perkawinanan religious differences. In addition it is also aimed to determine the implications of the Act No. 1 of 1974 on Marriage to Law No. 23 of 2006 on Population Administration. To achieve these objectives the research using normative juridical approach, with a secondary data source, the type of descriptive study with qualitative analysis. The study found that the validity of interfaith marriages according to Law Number 1 Year 1974 Article 2 paragraph (1) concerning Marriage, stated that the validity of marriage is based on their respective religions and beliefs. Some legal implications based on the Marriage Law are rights and obligations between husband and wife who have been ratified by a court through the establishment of judges which will result in the mixing of property for marriages that do not have marriage agreements and the birth of children creates reciprocal rights and obligations between parents and children . The implication based on the Population Administration Law is that the registration of marriage will get legal certainty for interfaith marriages that have obtained judges and children born who have not yet obtained a judge's decision to obtain a birth certificate.